Uluslararası Hukuk Süjesi Olarak Türkiye’deki Süryani Toplumu - Yalçınkaya, Alaeddin (FSM Vakıf Üniversitesi, 2022)
Ortadoğu’nun en eski toplumlarından biri olan Süryanilerin önemli bir kısmı başka ülkelere göç etmiş, bölgedeki nüfusunun büyük kısmını muhtelif nedenlerle kaybetmişlerdir. Anavatanları Kuzey Irak, Güneydoğu Türkiye ve Kuzeydoğu Suriye olmasına rağmen, göçler dolayısıyla başta Avrupa olmak üzere dünyanın birçok ülkesinde Süryani diasporaları oluşmuştur. Lozan Antlaşması’ndaki “gayrimüslim azınlıklar” olarak sadece Ermeni, Rum ve Yahudi toplumlar sayılmış olup bunun dışındakiler uzun süre azınlık kapsamındaki haklardan yararlanamamışlardır. Bu anlamda Türkiye’de yaşayan diğer gayrimüslim veya gayr-i Türklerin azınlık vasfı kabul edilmemiştir. Bu makalede Süryani toplumunun ortaya çıkışı, yaşadığı bölünmeler, bugünkü özellikleri ile Türkiye›deki Süryanilerin durumu özetlenmektedir. Uluslararası hukukta azınlık statüsü ışığında Türk Süryani cemaatinin bu kapsamdaki statüsü tahlil edilmektedir.

A significant part of the Syriacs, one of the oldest societies in the Middle East, immigrated to other countries and lost most of their population in the region for various reasons. Although their homelands are Northern Iraq, Southeast Turkey and Northeast Syria, Syriac diasporas have emerged in many countries of the world, especially in Europe, due to migrations. Only the Armenian, Greek and Jewish communities were taken into account as “non-Muslim minorities” in the Treaty of Laussanne, and others could not benefit from the rights as a minority. In this sense, the minority status of other non-Muslim or non-Turks living in Turkey has not been accepted. In this article, the emergence of the Syriac society, the experienced divisions, it’s current characteristics and the situation of the Syriacs in Turkey are summarized. In the light of the scope of minority status in International Law, the situation of the Turkish Syriac community in this context is analyzed.
Syriacs Community in Turkey as a Subject of International Law
Keywords: Süryaniler; Türk Süryani Cemaati; Azınlıklar; Lozan Antlaşması; Uluslararası Hukuk Süjesi; Syriacs; Turkish Syriac Community; Treaty of Lausanne; Subject of İnternational Law